2015
DOI: 10.2350/14-04-1471-pb.1
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives in Pediatric Pathology, Chapter 5. Gonadal Dysgenesis

Abstract: One of the most challenging areas in pediatric testicular pathology is the appropriate understanding and pathological diagnosis of disorders of sexual development (DSD), and in particular, the issue of gonadal dysgenesis. Here we present the main concepts necessary for their understanding and appropriate classification, with extensive genetic correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 233 publications
(240 reference statements)
0
15
0
2
Order By: Relevance
“…In this putative fetal stage of tissue development, germ cells reside apparently randomly distributed in an ovarian-like stroma or are arranged in primitive cord-like structures of immature supportive cells without forming ovarian follicles or testicular seminiferous cords ( Fig. 2 ) [Nistal et al, 2014a]. UGT is thought to be the precursor lesion for GB development [Cools et al, 2006b].…”
Section: Embryonic Formation Of Testis and Ovarymentioning
confidence: 99%
“…In this putative fetal stage of tissue development, germ cells reside apparently randomly distributed in an ovarian-like stroma or are arranged in primitive cord-like structures of immature supportive cells without forming ovarian follicles or testicular seminiferous cords ( Fig. 2 ) [Nistal et al, 2014a]. UGT is thought to be the precursor lesion for GB development [Cools et al, 2006b].…”
Section: Embryonic Formation Of Testis and Ovarymentioning
confidence: 99%
“…Seventeen of these patients (85%) were gonadectomized, and gonadoblastoma was found in 6 (35.3%). According to the classification of streak gonads [24][25][26], in our series, we found 9 cases of classic streak gonads, 7 of streak gonads with epithelial cord-like structures, and 1 streak testis. In the first group, we found an association between gonadoblastoma and dysgermino ma in 1 case, and in the second group, we found 5 gonadoblastomas and the coexistence in 1 of these cases of a dysgerminoma and an embryonal carcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…In the ovary the number of GCs decreases beginning prenatally and throughout childhood, 1921 such that by menarche virtually all GCs (follicles) are restricted to a narrow strip of cortex. Few studies have assessed testicular GC variability with age 12,13,22 but they demonstrate a prepubertal rise in testicular GC numbers, which is maintained into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…The gonads of patients with CAIS have a testicular morphology, often with Sertoli cell adenomas and/or hamartomatous nodules distorting the histological architecture. 8,11,13 In this study GC assessment was performed on the compressed testicular tissue found between these nodules.…”
Section: Methodsmentioning
confidence: 99%